OPTIMALISASI KONSENTRASI ASAM TARTRAT DAN WAKTU EKSTRAKSI PADA EKSTRAKSI PIGMEN BETASIANIN DARI KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) SEBAGAI PEWARNA ALAMI - Paranoan, Cindy Annike; Lahming, Lahming; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
The objectives of the research were (1) find out the concentration of tartrate acid (2) extraction timeof betacyanin on red dragon fruit skin.  The research employed  experimental research using Complete Randomized Design (CRD) factorial pattern by the concentration of tartrate acid 0.50%, 0.75%, 1% and 1.25% and extraction time 3 days, 4 days and 5 days. The obtained data were analyzed using analysis of variance (ANOVA). The result showed that (1) the extraction using tartrate acid concentration of 1% for3 days  (K3T1)  produced  the highest  level  of betacyanin content (2)  analysis of  pH  (3,  5,  6,  7, 8)  and temperature (40oC, 50oC, 60oC) showed the extraction of the red dragon fruit skin were stable at pH 7.Extract without treatment of optimum pH addition stabilized at 40oC, while the result of red dragon fruitskin’s extraction by addition of optimum pH stabilized at 50oC.